Estimating the Benefits of Bt Corn and Cost of Insect Resistance Management Ex Ante - Terrance M. Hurley; Ines Langrock; Kenneth Ostlie (Journal of Agricultural and Resource Economics, 2006)
This paper estimates farmer benefits for corn rootworm (CRW) active Bt corn and costs of complying with Environmental Protection Agency insect resistance management requirements. The estimates are obtained from farmer survey data that were collected in Minnesota in 2002, just prior to the commercial releases of CRW Bt corn. Benefit estimates range from $14 to $33.4 million, while compliance cost estimated range from $3.5 to $8.7 million depending on whether or not CRW Bt corn also controlled the European corn borer and whether of not it was approved for sale in major export markets.